Tri Hita Karana: (Sekilas Historis dan Hakikat Keharmonisan Semesta) - Putu Dana Yasa (Sphatika: Jurnal Teologi, 2022)
One of the concepts that Hindus have in providing an understanding of harmonious life is the emergence of the concept of tri hita karana. This concept has been widely known by Hindus, because this concept has been taught from an early age in the elementary school level. Theoretically, tri hita karana sounds so simple that humans must be able to establish a harmonious relationship with God, fellow humans and the environment. But in reality this concept has not been widely applied in life, so it is still a mere theoretical discourse. This is evidenced by the many problems of human harmony who have religion as a way of life. Tri hita karana is a concept of universal harmony which does not only include God's creation, but includes all components of the universe. The historical traces of the emergence of the concept of tri hita karana to date have proven that this concept must be understood and internalized in human life to achieve peace and harmony.